THE PLACE AND ROLE OF PSYCHOLOGICAL TRAINING FOR MILITARY SERVANTS (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article describes the theoretical foundations and recommendations for the formation of professional flexibility skills of future military personnel, as well as the role and role of psychological training for military personnel.